Monitoring of cognitive development in teaching programme ExpEdition: Can cognitive development reflect the influence of the learning environment? - Koperová, Dominika; Held, Ľubomír (Scientia in educatione, 2023)
An innovative view of science education is presented by the teaching programme ExpEdition – try, explore, discover. It offers the opportunity to teach science through systematically applied IBSE elements, space for teacher training and the preparation of appropriate teaching and methodological materials. The aim is to provide an insight into the monitoring of the cognitive development of long-term learners in the programme and at the same time to compare them with students learning in the traditional way, mostly by interpretation. The Inventory of Piaget’s Developmental Tasks (IPDT) test, which monitors the cognitive level attained by the pupil, and the Bipolar Statement Scale (BSS), which monitors the ability to grasp abstract content, were administered in the classroom. The results show a difference between lower secondary school pupils aged 14–15 years learning traditionally (12 schools, 14 classes, 287 pupils) and those learning by ExpEdition (2 schools, 4 classes, 83 pupils) in all the parameters studied (IPDT by 10 points, misconceptions by 2 points). Given that the results of the pupils involved in the programme appear to be significantly better than those of traditional pupils, it can be assumed that the learning environment created for the pupils in the project has a positive impact on their achievement.